ปัจจัยพยากรณ์ความเป็นผู้นำนักวิจัยของอาจารย์ในสถาบันอุดมศึกษาเอกชน - ชัยสุวรรณ, ศรุดา (Journal of Research and Curriculum Development, 2021)
The research purposes were as follows: 1) to study level of factors predictive and research leadership of Instructors in Private Higher Education Institutions 2) to analyze the relationship model of factors predictive and research leadership of instructors in private higher education Institutions 3) to analyze stepwise multiple regression analysis in assessing factors predictive of research leadership of instructors in private higher education Institutions. The participants consisted of 351 instructors in 2019. The research instrument was questionnaire with rating scales, content validity index item-objective congruence (IOC) of the questionnaire was at 0.80 - 1.00, and Cronbach's alpha as 0.98. The statistical methods used to analyze data were mean, standard deviation, Pearson's product moment correlation, stepwise multiple regression analysis. The results finding were follow: 1. The level of factors predictive research leadership of Instructors in Private Higher Education Institutions, as a whole and as individual aspect, at high level. Leadership behavior of administrators was rating the highest mean, the second highest mean was organizational culture, and organizational climate was rating the lowest mean. And research leadership of instructors in private higher education Institutions, as a whole and as individual aspect, at high level. Individual development was rating the highest mean, and achievement motivation, respectively. 2. Factors predictive and research leadership of instructors in private higher education Institutions were positively and significantly related to research leadership of instructors in private higher education Institutions at the level of .01 which was a very high level, when considering each perspective, it the revealed that there was a positive relationship between 0.705 - 0.796. Leadership behavior of administrators had more positive relationship with the research leadership of instructors in private higher education Institutions than other factors predictive. 3. Five out of six factors were found related to the research leadership of instructors in private higher education Institutions at very high level. Multiple correlation coefficient was at 0.866. The prediction of the research leadership of instructors in private higher education Institutions made by variables was at 75.0 percent. Variables that can be used to predict the research leadership of instructors in private higher education Institutions with statistical significance at 0.01 level were leadership behavior of administrators (X6), administrators value (X5), knowledge management (X4), organizational culture (X1), organizational climate (X2), The regression equation of standard scores was as follows: Z = .796 (X6) +.477 (X5) +.432 (X4)+.397 (X1) +.382 (X2)